Tissue vibration in prolonged running - Friesenbichler, B.; Stirling, L. M.; Federolf, P.; Nigg, B. M. (Journal of Biomechanics, 2011)
The impact force in heel-toe running initiates vibrations of soft-tissue compartments of the leg that are heavily dampened by muscle activity. This study investigated if the damping and frequency of these soft-tissue vibrations are affected by fatigue, which was categorized by the time into an exhaustive exercise. The hypotheses were tested that (H1) the vibration intensity of the triceps surae increases with increasing fatigue and (H2) the vibration frequency of the triceps surae decreases with increasing fatigue. Tissue vibrations of the triceps surae were measured with tri-axial accelerometers in 10 subjects during a run towards exhaustion. The frequency content was quantified with power spectra and wavelet analysis. Maxima of local vibration intensities were compared between the non-fatigued and fatigued states of all subjects. In axial (i.e. parallel to the tibia) and medio-lateral direction, most local maxima increased with fatigue (supporting the first hypothesis). In anterior-posterior direction no systematic changes were found. Vibration frequency was minimally affected by fatigue and frequency changes did not occur systematically, which requires the rejection of the second hypothesis. Relative to heel-strike, the maximum vibration intensity occurred significantly later in the fatigued condition in all three directions. With fatigue, the soft tissue of the triceps surae oscillated for an extended duration at increased vibration magnitudes, possibly due to the effects of fatigue on type II muscle fibers. Thus, the protective mechanism of muscle tuning seems to be reduced in a fatigued muscle and the risk of potential harm to the tissue may increase.